2020
DOI: 10.1111/plb.13198
|View full text |Cite
|
Sign up to set email alerts
|

Root discoloration and shoot symptoms in silver birch afterPhytophthorainfectionin vitro

Abstract: • There are no records of established plant pathogenic Phytophthora species in Finnish forests, but they are likely in the future. Therefore, the effects of Phytophthora inoculations on young, ca. 2-month-old silver birch (Betula pendula) seedling roots and shoots were investigated. • Visual inspection of dark discoloration, direct PCR and re-isolation, and detailed root morphology analyses were used to evaluate the effects of Phytophthora inoculation on roots. Symptoms in leaves and stems were also recorded. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…and P. abies , moderate lesions on B. pendula , and no infections on Q. robur or P. sylvestris [ 129 ]. In an in vitro study using two-month-old B. pendula , roots inoculated with P. cactorum often showed dark discolorations, loss of fine roots, and decreased branching [ 126 ], even though discolorations are not a specific symptom of Phytophthora infections [ 127 ]. The symptoms of the aboveground parts included reduced height growth, lower chlorophyll fluorescence, significantly longer dark or brown discolorations in the stems, and a higher proportion of brownish and wilting leaves [ 126 ].…”
Section: Characteristics Of Phytophthora Species D...mentioning
confidence: 99%
See 1 more Smart Citation
“…and P. abies , moderate lesions on B. pendula , and no infections on Q. robur or P. sylvestris [ 129 ]. In an in vitro study using two-month-old B. pendula , roots inoculated with P. cactorum often showed dark discolorations, loss of fine roots, and decreased branching [ 126 ], even though discolorations are not a specific symptom of Phytophthora infections [ 127 ]. The symptoms of the aboveground parts included reduced height growth, lower chlorophyll fluorescence, significantly longer dark or brown discolorations in the stems, and a higher proportion of brownish and wilting leaves [ 126 ].…”
Section: Characteristics Of Phytophthora Species D...mentioning
confidence: 99%
“…In an in vitro study using two-month-old B. pendula , roots inoculated with P. cactorum often showed dark discolorations, loss of fine roots, and decreased branching [ 126 ], even though discolorations are not a specific symptom of Phytophthora infections [ 127 ]. The symptoms of the aboveground parts included reduced height growth, lower chlorophyll fluorescence, significantly longer dark or brown discolorations in the stems, and a higher proportion of brownish and wilting leaves [ 126 ]. Furthermore, inoculation trials on three-month-old B. pendula and A. glutinosa seedlings showed that P. cactorum was able to kill 40% of the B. pendula seedlings, but caused only small lesions on 40% of A. glutinosa seedlings [ 128 ].…”
Section: Characteristics Of Phytophthora Species D...mentioning
confidence: 99%